Age-associated DNA methylation changes in naive CD4+ T cells suggest an evolving autoimmune epigenotype in aging T cells. (April 2017) - Dozmorov, Mikhail G; Coit, Patrick; Maksimowicz-McKinnon, Kathleen; Sawalha, Amr H
Aim: We sought to define age-associated DNA methylation changes in naive CD4 + T cells.Materials & methods: Naive CD4 + T cells were collected from 74 healthy individuals (age 19–66 years), and age-related DNA methylation changes were characterized.Results: We identified 11, 431 age-associated CpG sites, 57% of which were hypermethylated with age. Hypermethylated sites were enriched in CpG islands and repressive transcription factor binding sites, while hypomethylated sites showed T cell specific enrichment in active enhancers marked by H3K27ac and H3K4me1. Our data emphasize cancer-related DNA methylation changes with age, and also reveal age-associated hypomethylation in immune-related pathways, such as T cell receptor signaling, FCγR-mediated phagocytosis, apoptosis and the mammalian target of rapamycin signaling pathway. The MAPK signaling pathway was hypermethylated with age, consistent with a defective MAPK signaling in aging T cells.Conclusion: Age-associated DNA methylation changes may alter regulatory mechanisms and signaling pathways that predispose to autoimmunity.